Paths out of poverty: International experience - Fan, Shenggen; Cho, Emily EunYoung (Chinese Academy of Agricultural Sciences, 2021)
The global community has committed, as the first priority of the Sustainable Development Goals (SDGs), to end poverty in all its forms everywhere. While the decline of global poverty continues, progress has slowed and remains uneven through different parts of the world. To ensure that no one is left behind in China and beyond, research will be critical to inform paths out of poverty. In this regard, it is valuable to take stock of international experiences and the various pathways out of poverty with a focus on agriculture. Africa’s agricultural growth has been largely driven by land expansion and poverty reduction has been slowest among all regions. South Asia agriculture has been led by diversification of smallholder agriculture and its poverty reduction impact has been large, but its future poverty reduction is limited by rural-urban migration and lack of formal jobs in urban centers. Social protection programs have been used by many Latin American countries as the region is more urbanized than any other developing regions. China’s agricultural and economic success was driven by agriculture-led reforms and rural development. These changes brought significantly higher incomes among rural residents, which accounted for highest initial levels of poverty and hunger, and in increased availability of food at affordable prices. Investments in nutrition, health, education, clean water, and good sanitation also complemented progress. The foremost lesson is that smallholder-led agriculture growth in land scarce countries often have the largest impact on poverty reduction. Secondly, nonfarm employment and rural-urban migration must follow once agricultural productivity has reached a certain level. However, pre-mature exiting from agriculture can do more harm. Thirdly, even before large scale poverty reduction through sectoral and regional development is exhausted, social safety nets must be established to cover those who have not benefited from growth and development. Productive social safety nets have proven to be cost-effective in many countries. Urban poverty should also be part of the protection scheme when large proportion of rural population moves to cities.